PO068 The similarities between spontaneous and nitroglycerin-triggered premonitory symptoms in migraineurs. (1st December 2017) - Karsan, Nazia; Bose, Pyari; Thompson, Charlotte; Goadsby, Peter
Abstract : Human models of migraine are required to understand the neurobiology of this disabling condition. Nitroglycerin (NTG) effectively triggers migraine headache in 60%–70% of migraineurs, and has also been shown to trigger premonitory symptomatology. We aimed to study the triggering of premonitory symptomatology with NTG, comparing the phenotype of triggered attacks to spontaneous attacks. Migraineurs who reported spontaneous premonitory symptoms were recruited following informed consent (n=49). A detailed migraine history was taken from each subject at screening. NTG (0.5 mcg/kg/min over 20 min) was administered intravenously to each subject. The phenotype of premonitory symptoms where present (n=47) following triggering was recorded for each subject. Statistical analyses were performed to assess the correlation between common spontaneous and triggered symptoms using the Chi-squared test. p<0.05 was considered significant. Analyses were performed for fatigue, concentration difficulty, irritability, neck stiffness and yawning. Triggered premonitory symptomatology was similar to spontaneous symptomatology, with a statistically significantly increased likelihood of reporting most of the common symptoms following triggering if reported in spontaneous attacks (fatigue, neck stiffness, irritability and yawning). There was a trend towards significance for concentration difficulty (p=0.053). The similarities between spontaneous and triggered attacks suggest that NTG triggering is an effective model to study human migraine.